2006
DOI: 10.1111/j.1745-7262.2006.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological changes of the testis and epididymis in adult rats as a result of Ley dig cell destruction after ethane dimethane sulfonate treatment: a morphometric study

Abstract: The primary spermatogenic lesions following EDS administration were (i) spermiation failure and (ii) detachment of spermatids and spermatocytes associated with impairment in spermiogenesis and meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 19 publications
5
31
0
Order By: Relevance
“…Only few elongated and elongating spermatids existed in the seminiferous epithelium and degenerating round spermatids and spermatogenic cells being observed in the lumen. These changes indicate impairment in meiosis (development of spermatids from spermatocytes) and spermatogenesis (transformation of elongated spermatids from round spermatids) 25. Spermatid degeneration observed in the present study or apoptosis observed previously26 was likely another factor in the reduction of spermatid numbers.…”
Section: Discussionsupporting
confidence: 66%
“…Only few elongated and elongating spermatids existed in the seminiferous epithelium and degenerating round spermatids and spermatogenic cells being observed in the lumen. These changes indicate impairment in meiosis (development of spermatids from spermatocytes) and spermatogenesis (transformation of elongated spermatids from round spermatids) 25. Spermatid degeneration observed in the present study or apoptosis observed previously26 was likely another factor in the reduction of spermatid numbers.…”
Section: Discussionsupporting
confidence: 66%
“…Androgen deficiency disturbs spermiation process by altering spermatid-Sertoli cell junctions; which results in premature detachment of round spermatids from Sertoli cells and seminal epithelium [20]. Decreased testosterone levels have been associated with alterations in Sertoli and Leydig cells [23]. Treatment with different parts of the plants such as leaf powder of Azadirachta indica [24,25] crude garlic [23] and benzene extract of O. sanctum leaves [22] on ultrastructure of the rat testis revealed several changes and it can be summaries in three categories such as: (i) vacuolization in the Sertoli cells and germ cells; (ii) degeneration of mitochondria followed by vacuolization in spermatocytes and spermatids; and (iii) a decrease in nuclear density and ruptures of plasmatic membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased testosterone levels have been associated with alterations in Sertoli and Leydig cells [23]. Treatment with different parts of the plants such as leaf powder of Azadirachta indica [24,25] crude garlic [23] and benzene extract of O. sanctum leaves [22] on ultrastructure of the rat testis revealed several changes and it can be summaries in three categories such as: (i) vacuolization in the Sertoli cells and germ cells; (ii) degeneration of mitochondria followed by vacuolization in spermatocytes and spermatids; and (iii) a decrease in nuclear density and ruptures of plasmatic membranes. Studies from Aladakatti and Nazeer Ahamed [22,24] and Alladakatti et al [25] have shown that Azadirachta indica leaf powder and benzene extract of Ocimum sanctum leaves cause the disruption of intercellular bridges between germ cell-germ cells, germ cells-Sertoli cells or Sertoli cells-Sertoli cells in rats due to their antiandrogenic properties.…”
Section: Discussionmentioning
confidence: 99%
“…71 As early as 7 d after administration of a single dose of EDS round spermatids can be found in the lumen of the epididymis. 72 The number of mature sperm contained in the epididymis is decreased 60% by day 7 and 80% by day 12 following EDS exposure. Moreover, neutrophilic nuclei were evident within the lumen by day 12.…”
Section: Androgen Deprivation In the Adultmentioning
confidence: 99%